2012
DOI: 10.1017/s002185961200038x
|View full text |Cite
|
Sign up to set email alerts
|

Potential and realities of enhancing rapeseed- and grain legume-based protein production in a northern climate

Abstract: SUMMARYCrop-based protein self-sufficiency in Finland is low. Cereals dominate the field cropping systems in areas that are also favourable for legumes and rapeseed. The present paper estimated the realistic potential for expanding protein crop production taking account of climatic conditions and constraints, crop rotation requirements, field sizes, soil types and likelihood for compacted soils in different regions. The potential for current expansion was estimated by consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 81 publications
0
26
0
Order By: Relevance
“…The Finnish dependency on imported soya bean could be reduced by increasing the cultivation of protein crops, with some authors favoring the regionally traditional field pea and turnip rape, in spite of the low yield and high fertilizer requirements of the latter, 18 and others favoring higher-protein legumes such as faba bean and agricultural lupins. 9 Hence we set out to explore the possibility to produce plant protein for food and feed uses from a range of grain legume species, focusing on cultivars that might be adapted to short growing seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The Finnish dependency on imported soya bean could be reduced by increasing the cultivation of protein crops, with some authors favoring the regionally traditional field pea and turnip rape, in spite of the low yield and high fertilizer requirements of the latter, 18 and others favoring higher-protein legumes such as faba bean and agricultural lupins. 9 Hence we set out to explore the possibility to produce plant protein for food and feed uses from a range of grain legume species, focusing on cultivars that might be adapted to short growing seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Pea (Pisum sativum L.) is a minor crop in Finland, which was cultivated on some 12000 hectares in 2015 (corresponding to ~0 .5 % of cultivated area), of which 2700 hectares were organic (www.stat.luke.fi/en). However, due to the warming climate-induced potential for longer growing seasons and subsequent higher yields, an expansion of pea cultivation from its current minor and regionally localized production is appealing (Peltonen-Sainio et al 2009, Peltonen-Sainio et al 2013. In general, pea exhibits high variation in yield and quality at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Von Richthofen et al (2006) examined the cultivation of grain legumes in rotation with cereal crops and oilseeds in France and Germany and found that mineral fertilization, pesticide use, and cultivation costs decreased, while the yield of the subsequent crop increased (similar findings can be found in Nevens andReheul 2001 andHuang andUri 1993 for maize, and in Preissel et al's 2015 European review). With increased use of legumes many countries could furthermore improve their self-sufficiency in protein and nitrogen (see de Visser et al 2014 for the European Union (EU); and Peltonen-Sainio et al 2013;and Nykänen et al 2012 for Finland).…”
Section: Introductionmentioning
confidence: 99%